The Evaluation of p16ink4a Immunoexpression/Immunostaining and Human Papillomavirus DNA Test in Cervical Liquid-Based Cytological Samples. Issue 1 (1st January 2011) - Nasioutziki, Maria; Daniilidis, Angelos; Dinas, Kostos; Kyrgiou, Maria; Valasoulis, George; Loufopoulos, Panagiotis D.; Paraskevaidis, Evaggelos; Loufopoulos, Aristotelis; Karakitsos, Petros
Abstract : Aim: To evaluate the role of p16INK4a immunoexpression and human papillomavirus (HPV) DNA test for the detection of dyskaryotic cells in high-risk women. Materials and Methods: This work was a retrospective diagnostic study conducted in the University Hospital of Thessaloniki from January to December 2008. The subjects were women with current or previous HPV infection and current or previous cervical intraepithelial lesion (with or without treatment) or clinical warts. All liquid-based cytological samples were tested for P16INKa and HPV DNA test. The accuracy parameters used for the outcome included sensitivity, specificity, and positive predictive value. Results: A total of 226 women were included; the mean age was 29 years. Expression of p16INK4a was detected in the cytological samples of 13% of the negative cases, 44% of the cases of atypical squamous cells of undetermined significance, 46% of the cases of low-grade squamous intraepithelial lesion, and 78% of the cases of high-grade squamous intraepithelial lesion. A total of 91 women tested positive for high-risk HPV infection, and 54 of those had p16INK4a-positive staining reaction cells. The concordance between the 2 tests, HPV DNA and p16, was 59% regarding infection-positive cases. Diffuse strong parabasal p16INK4a immunostaining (nuclear score >2) was observed in 17 cases of the abnormal cytological findings (atypical squamous cells of undetermined significance, 2 cases; low-grade squamous intraepithelial lesion, 8 cases; high-grade squamous intraepithelial lesion, 7 cases). Colposcopy-directed biopsies were used as the criterion standard for the detection of cervical intraepithelial neoplasia in 91 women. The sensitivity of p16INK4a was 95% and the specificity was 92%, whereas the sensitivity of high-risk HPV was 100% and the specificity was 78%. The positive predictive value of p16INK4a was 71%, whereas that of HPV DNA was 44%. Conclusion: The findings suggest that p16INK4a immunostaining can improve the accuracy of cytological examination and HPV DNA test and may be particularly useful in the triage of low-grade lesions.